Rethinking Design Theory in Information Systems - Venable, John (Springer Berlin Heidelberg, 2013)
Design Theory has been written about extensively in InformationSystems (IS), but remains heavily problematic. Some researchers explicitly excludedesign theory as an outcome of Design Science Research (DSR), othersdisagree about the form and purpose of design theories, many consider designtheories to be too complicated to construct, some journal editors and researchersgive low priority to design theory, and very few DSR publications propose designtheories.This paper reviews and critically examines the IS literature on design theories,the nature of technological design artefacts compared to phenomena in thenatural, biological, and social domains, and whether design theory is ‘prescriptive’or ‘explanatory’.Using a DSR approach, the paper makes recommendations concerning theform and use of design theory, in order to move toward a resolution of the disagreementsabout design theory and progress the development of clearer andmore useful formalisations of knowledge for practical use.